Postcolonial Identity in The Inheritance of Loss - Shrestha, Ravi Kumar (Patan Prospective Journal, 2022)
This research article deals with the postcolonial identity of the Indian immigrant characters delineated in The Inheritance of Loss written by Kiran Desai, a noted diasporic novelist of Indian origin. The study reveals that the identity of South Asians or Indian immigrants in the diaspora is changed and weakened by the colonialism in such a way that even in the postcolonial era the life of the immigrants reflects the influence of cultural colonialism. On the one hand, these Indian immigrants who are portrayed as immigrant characters in the western location happen to migrate in the hope of embracing white privileges in the form of better opportunities such as higher education, jobs, social security and so on; on the other hand, they face cultural clashes and have identity crisis. They mimic the western culture as a part of survival strategy. As a result, they feel culturally displaced, unhomed, racially segregated, develop hybrid identity and find divided identity. Regarding methodology, the qualitative research method is applied. As for theory, the postcolonial theory is applied along with theoretical concepts such as Homi K. Bhabha’s Hybridity and Mimicry, desiring whiteness of Kalpana Seshadri-Crooks and Frantz Fanon, and Stuart Hall’s Diaspora and Identity. The theoretical framework has been prepared and used to analyse the postcolonial identity of the major characters such as Biju, Jemubhai Patel and so on.